NOTAS - O CAOS E A INTERDISCIPLINARIDADE - Ernani Ribeiro de Almeida; Fabiana Ribeiro de Almeida; Franciana Pedrochi; Gisele Strieder Phippsen; Francielle Sato; Gustavo Max Dearo Simonetti; Iara Frangiotti Mantovani; Iris Antônio Maeda; Kelly Christine da Silva; Kleto Michel Zan; Marcelo Freitas de Andrade; Mônica Bordim Sanches; et al. (Arquivos do Mudi, 2012)
O presente artigo busca dar uma visão geral sobre a teoria do caos e suas aplicações.